Research on Measurement Methods of Radiation Dose in DSA Diagnosis - XIONG Wenjun, BO Yuqi, LIU Hongkai, HUANG Jinfeng, HUA Chengbin (Journal of Isotopes, 2024)
Doctors have to perform surgery under the guidance of X-rays during DSA intervention diagnosis. Long-term surgery may cause excessive radiation exposure to doctors. It is necessary to develop a small real-time radiation detector to measure the radiation exposure of the different tissues during the surgery, identify weak points in radiation shielding, and develop safer shielding plans. Based on chip technology, we developed a miniaturized, low-power, real-time radiation dose measurement module, which can be easily worn on the hand for real-time measurement of radiation dose. Using the MCNP simulation program, the energy response curve of the detector was calculated under different compensation thicknesses, and the optimal thickness of the compensation was obtained. Various parameters of the measurement module, such as repeatability, dose linearity, energy response, and radiation tolerance dose, were tested and verified. The results showed that the weight of the measurement module was less than 15 g, the volume was less than 15 mm×10 mm×5 mm, the upper limit of dose rate could be extended to 1 Sv/h, and the energy response was better than ±30% in the range of 10~250 keV. The radiation tolerance dose was better than 100 Gy. This work solved the problem of miniaturization of real-time radiation detector, provided radiation real-time measurement methods of exposure dose on the hand for doctors in DSA diagnosis and treatment, measuring X-ray. Through analysis of post data, it can analyze the radiation risk during the surgical process, thus providing technical means and data support for optimization of radiation protection.